1945
DOI: 10.1063/1.1723985
|View full text |Cite
|
Sign up to set email alerts
|

Free Volume and Entropy in Condensed Systems III. Entropy in Binary Liquid Mixtures; Partial Molal Entropy in Dilute Solutions; Structure and Thermodynamics in Aqueous Electrolytes

Abstract: The ideas of the first and second papers in this series, which make it possible to interpret entropy data in terms of a physical picture, are applied to binary solutions, and equations are derived relating energy and volume changes when a solution is formed to the entropy change for the process. These equations are tested against data obtained by various authors on mixtures of normal liquids, and on solutions of non-polar gases in normal solvents. Good general agreement is found, and it is concluded that in su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

26
693
3
10

Year Published

1972
1972
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,721 publications
(747 citation statements)
references
References 41 publications
26
693
3
10
Order By: Relevance
“…13 C chemical shift data to show that CH 4 gas in water has a hydration shell with 20 water molecules. They made "magic angle" spinning experiments on crystalline fire ice at subzero temperatures and reported that CH 4 in the small domain of the Type I clathrate structure has a different chemical shift (−3.6 ppm) than the species CH 4 -24 that is present in the large domain of fire ice. Species CH 4 -24 has 24 waters and a 13 C chemical shift of −5.9 ppm (12), whereas the small domain of Type I clathrate is known to contain 20 waters (10).…”
Section: Resultsmentioning
confidence: 99%
“…13 C chemical shift data to show that CH 4 gas in water has a hydration shell with 20 water molecules. They made "magic angle" spinning experiments on crystalline fire ice at subzero temperatures and reported that CH 4 in the small domain of the Type I clathrate structure has a different chemical shift (−3.6 ppm) than the species CH 4 -24 that is present in the large domain of fire ice. Species CH 4 -24 has 24 waters and a 13 C chemical shift of −5.9 ppm (12), whereas the small domain of Type I clathrate is known to contain 20 waters (10).…”
Section: Resultsmentioning
confidence: 99%
“…Today there are mainly two opposing views (12) on the hydrophobicity of water: either it is caused chiefly by the small size of the water molecule (13) or by the perturbed H-bonded water structure around nonpolar groups (the iceberg model) (1,7,8).…”
Section: The Polar Group Effectmentioning
confidence: 99%
“…The polar group effect can be understood by the iceberg model of Frank and Evans (7) and Kauzmann (1,8). In the iceberg model, the hydrophobic free energy arises chiefly from the perturbed H-bonded structure of water that develops around nonpolar groups (1,7,8). Using the iceberg model, the polar group effect is explained as the result of strong interactions between water and polar groups that affect the perturbed water structure around nearby nonpolar groups.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of osmolyte action continues to be controversial. Opposing positions favor either a direct interaction between protein and osmolyte (8)(9)(10)(11), such as hydrogen bonding, or an indirect effect mediated by the alteration of water structure (12,13), or a mixture of both (14)(15)(16)(17)(18)(19). It has been difficult to distinguish between these direct and indirect models because the osmolyte-protein interaction is so weak.…”
mentioning
confidence: 99%